Catingueira garante produção de caprinos e ovinos na seca extrema. - CAVALCANTE, A. C. R. (2013)
Disponível em: <http://www.zoonews.com.br/noticias2/noticia.php?idnoticia=229429>. Acesso em: 14 set. 2013.